A case study of strategy implementation at a major Eastern Cape component supplier company in the automotive industry - Koyana, Gwyneth Puseletso (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
A review of the literature on strategy implementation reveals that there is limited knowledge on how strategies should be implemented. This thesis focuses on a case study of strategy implementation at a major Eastern Cape component supplier company in the automotive industry, for purposes of establishing how the company implemented its strategies to become one of the best cost leaders in the manufacture of automotive pressed metal body components in South Africa. Data collated from the company is analysed and discussed with a resultant description of how the research participants understood the process of strategy implementation within the research company during the period January 2006 to December 2007. Interviews were undertaken within the levels of top management, middle management and the operational employees. Interpretations were made of the constructs made by the research participants in their understanding of how the research company implemented its strategy to become one of the best cost leaders in the manufacture of automotive pressed metal body components. It transpired from the findings of the research that the research company manufactured 70% of its products for one major client. During the manufacture of its products, the research company had to conform to the quality standards required by the main client. The main client was therefore offered the desired service at the best price. The strategy of the research company was to strive to be one of the best cost leaders in the manufacture of its products. It sought to do this by producing high quality products. Analysis is made of the strategic content, strategic context, operational processes and outcomes for the research company after the implementation of its strategy. It emerges in the case study that the strategy implementation factors cannot be considered separately in linear models but holistically, since one implementation factor may influence the others, resulting in a context and process based approach.
Keywords: Automobile industry and trade -- South Africa -- Eastern Cape; Automobile industry workers -- South Africa -- Eastern Cape; Industrial organization -- South Africa -- Eastern Cape -- Case studies; Strategic planning -- South Africa -- Eastern Cape -- Case studies